Impact of Phosphorus Restriction and Vitamin D-Substitution on Secondary Hyperparathyroidism in a Proteinuric Mouse Model - Bernhard N. Bohnert; Christoph Daniel; Kerstin Amann; Jakob Voelkl; Ioana Alesutan; Florian Lang; Nils Heyne; Hans-Ulrich Häring; Ferruh Artunc (Karger Publishers, 2015)
Background/Aims: Since the discovery of FGF23, secondary hyperparathyroidism (SHPT) in renal disease has been considered to result primarily from phosphorus retention rather than vitamin D deficiency. However, the impact of phosphorus restriction and vitamin D supplementation on SHPT is still ill defined. Methods: We investigated the development of SHPT in a doxorubicin-induced proteinuric mouse model and tested different treatment strategies including a low phosphorus diet and substitution with native or active vitamin D in 129 S1/SvImJ wild-type mice. Results: Development of SHPT at day 30 was strongly related to the magnitude of induced proteinuria. In mice with a proteinuria 100 mg/mg creatinine) developed marked SHPT (PTH increase 10.1-fold) accompanied by massive increase in FGF23 (27.0-fold increase), hyperphosphatemia (1.8-fold increase), renal failure (7.3-fold urea increase) and depletion of both 25-OH vitamin D and 1,25-OH vitamin D. Substitution with native or active vitamin D was unable to suppress SHPT, whereas a low-phosphorus diet (Pi content 0.013%) completely suppressed SHPT in mice with both mild and heavy proteinuria. Conclusions: The development of SHPT resulted from phosphate retention in this proteinuric model and could completely be suppressed with a low-phosphorus diet.